Autoimmune Polyglandular Syndrome Type 2 In A Patient With Peripartum Cardiomyopathy - Daniel C. Rafii, MD; Patricia Park, MD; Christine A. Resta, MD (AACE Clinical Case Reports, 2017)
ABSTRACT: Objective: To present a case of concomitant peripartum cardiomyopathy and autoimmune polyglandular syndrome type 2 during pregnancy.Methods: Clinical presentation during pregnancy and literature review.Results: A 32-year-old woman at 34 weeks gestational age was referred to our hospital out of concern for pre-eclampsia. She had been diagnosed with autoimmune hypothyroidism during pregnancy. During induction of labor, the patient was intubated for impending respiratory failure. An echocardiogram performed that day revealed a reduced ejection fraction (EF) of 45% and global cardiomyopathy. Post-partum, the patient was noted to be hypotensive and hypoglycemic. Random serum cortisol was 1.2 μg/dL. The patient improved clinically after a course of corticosteroids. Subsequently, a cosyntropin stimulation test confirmed adrenal insufficiency. Plasma adrenocorticotropic hormone was elevated >1,250 pg/mL, confirming primary adrenal insufficiency.Conclusion: Despite its rarity, adrenal insufficiency during pregnancy can significantly increase the risk of unfavorable pregnancy outcomes, morbidity, and mortality. The clinical presentation of adrenal insufficiency can be obfuscated by symptoms normally attributed to pregnancy. Peripartum cardiomyopathy is a diagnosis of exclusion after other causes of heart failure are ruled out. There are various proposed mechanisms for the pathogenesis of peripartum cardiomyopathy, including autoimmune processes. Recognition of this possible link should prompt clinicians to heighten their awareness of the potential risk of developing peripartum cardiomyopathy in women with other autoimmune conditions. Conversely, in women who develop peripartum cardiomyopathy, investigation for a concomitant autoimmune condition may also be indicated.Abbreviations: APS = autoimmune polyglandular syndrome